2007
DOI: 10.1158/0008-5472.can-07-2464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Resveratrol Action in Lung Cancer Cells Using Dual Protein and Microarray Analyses

Abstract: Resveratrol, a natural phytoestrogen found in red wine and a variety of plants, is reported to have protective effects against lung cancer; however, there is little work directed toward the understanding of the mechanism of its action in this disease. In this study, we used a combination of experimental approaches to understand the biological activity and molecular mechanisms of resveratrol. Microarray gene expression profiling and high-throughput immunoblotting (PowerBlot) methodologies were employed to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 32 publications
(37 reference statements)
7
82
0
2
Order By: Relevance
“…Furthermore, microarray studies regarding cellular responses to D3T or resveratrol have failed to implicate alterations in membrane transport (Kwak et al, 2003;Whyte et al, 2007). Despite these data, transport and repair have not been explicitly evaluated in this study and cannot be excluded as possible factors contributing to cytotoxicity.…”
Section: Human Ptgr1 Activates Acylfulvenes and Improves Efficacy 431mentioning
confidence: 86%
“…Furthermore, microarray studies regarding cellular responses to D3T or resveratrol have failed to implicate alterations in membrane transport (Kwak et al, 2003;Whyte et al, 2007). Despite these data, transport and repair have not been explicitly evaluated in this study and cannot be excluded as possible factors contributing to cytotoxicity.…”
Section: Human Ptgr1 Activates Acylfulvenes and Improves Efficacy 431mentioning
confidence: 86%
“…It possesses the ability to scavenge oxidatively generated free radicals, and prevents tumor progression by blocking NF-B expression, leading to cancer cell apoptosis 16,[23][24][25][26][27] . RV also has promising neuroprotective and cardioprotective effects, as well as slowing aging and delaying the onset of chronic diseases 23,[28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Resveratrol inhibits cancer cell growth in many cell lines, including cancers of the lung, prostate, colon, breast and ovaries. [3][4][5][6][7][8][9][10][11][12][13][14] Resveratrol also reduces tumor incidence in animal models by interfering with carcinogenesis through a wide array of anti-cancer actions. Several animal studies have demonstrated the ability of resveratrol to inhibit prostate cancer development by downregulating androgen receptors, inducing apoptosis/cell cycle arrest and inhibiting disease progression.…”
mentioning
confidence: 99%